Framing pictures : film and the visual arts - Jacobs, Steven (Edinburgh : Edinburgh University Press, 2011)
1. Camera and Canvas: Emmer, Storck, Resnais and the Post-War Art Film##2. Vasari in Hollywood: Biopics and Artists ##3. Galleries of the Gaze: Museums in Rossellini's Viaggio in Italia and Hitchcock's Vertigo ##4. Tableaux Vivants 1: Painting, Film, Death and Passion Plays in Pasolini and Godard ##5. Tableaux Vivants 2: Film Stills and Contemporary Photography ##6. The Video That Knew Too Much: Hitchcock, Contemporary Art and Post-Cinema
boek